Impact of Citrus Greening on Citrus Operations in Florida - Ariel Singerman; Pilar Useche (EDIS)
Florida is the largest orange-producing state in the United States and the third largest orange producer in the world, but the Florida citrus industry and its position in the global citrus market are being jeopardized by a bacterial disease known as citrus greening or Huanglongbing (HLB). HLB hurts the vascular systems of citrus trees and prevents them from absorbing nutrients. The disease reduces yields, leads to smaller, lower-quality fruit, kills trees, and increases farmers’ production costs. First found in Florida in 2005, HLB has spread rapidly across the state.